Applying a Strict Discovery Rule to Art Stolen in the Past - Preziosi, Tarquin (1997)
There is a great deal of un-recovered stolen art, and a great deal of confusion within and among jurisdictions as to when the applicable statute of limitations for stolen art begins to run. Holistic legal reform in this area is long overdue. Recent proposals, responding to current practices in the art world, call for the adoption of an art theft registry to help effectuate the return of stolen art and provide efficiency in the marketplace. However, a great number of objects fall outside the effective scope of these proposals: art that was stolen in the past, and those artworks which are not subject to effective registration. This Note suggests that these twin problems of retroactivity and non-registrability are best dealt with by the adoption of a strict discovery rule. This rule provides that the statute of limitations does not begin to run until the true owner becomes aware of the identity of the possessor of his or her artwork-irrespective of the owner's diligence in searching for the art. This Note thus proposes a two-part solution to the problems inherent in determining when the statute of limitations for stolen art begins to run: (1) future victims of art theft would be required to register their stolen artwork in order to toll the statute of limitations; and (2) victims of past thefts, or future victims of art theft whose artworks are not registrable, will have the statute of limitations tolled until they become aware of the identity of the current possessor of their artworks